The Mediating Role of Service Quality, Tourists’ Satisfaction and Destination Trust in the Relationship between Destination Image and Tourist Revisiting Intention - SIREGAR, M. Ridha; SIREGAR, Muhammad Ilhamsyah; SAPUTRA, Jumadil; MUZAMMIL, Abdul; MUHAMMAD, Zikri (Journal of Environmental Management and Tourism, 2021)
Tourism industry turns out to be a large international industry with enormous growth potential. Based on previous studies, Islamic tourism is popular among Muslim tourists. Thus, satisfying Muslim tourists with the image of a religious destination can encourage them to travel and revisit the destination in the future. The aim of this study was to determine the effect of destination image on intention of tourist to revisit the destination mediated by service quality, tourists’ satisfaction and destination trust in Shariah tourism destinations in Aceh. This study was conducted on 420 domestic and foreign tourist that come to visit Aceh. This study is included in the type of descriptive-quantitative research using survey method. The sample taken by using purposive sampling technique and the sample data were statistically analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with second order method and Multiple Group Analysis for gender. The results showed that the destination image directly had a significant effect on service quality, tourist satisfaction, destination trust and revisit intention, and indirectly the destination's image has an influence on the revisit intention through the service quality and destination trust, but not through tourists’ satisfaction. Whereas, according to gender of male, there is no influence was found between tourists’ satisfaction and destination trust to revisit intention.